Experimental study, phenomenological and adaptive neuron analysis of creep property of Momordica augustisepala L nanofiber reinforced polyvinyl alcohol polymer film composite. Issue 1 (March 2020) - Adeyi, A J; Durowoju, M O; Adeyi, O
Abstract: The viscoelastic property of packaging material affects foods' postharvest management and biophysical quality preservation of food. This study investigated the creep viscoelastic property of neat polyvinyl alcohol film and polyvinyl alcohol film reinforced Momordica augustisepala nanofiber composite. The applicability and comparison of Burger phenomenological and Adaptive neuron model to analyze the creep data were investigated. The instantaneous modulus and creeping speed of neat and reinforced polyvinyl alcohol were 7.53710 MPa, 10.27580 MPa and 3.00590 MPa.s, 2.85391 MPa.s, respectively. The coefficient of determination of Burger model prediction was 0.99889 and 0.99972 for neat and composite polyvinyl alcohol film, while the coefficient of determination of Adaptive neuron model was 0.99986 for both neat and reinforced polyvinyl alcohol film. The Momordica augustisepala nanofiber improved the creep viscoelastic property of polyvinyl alcohol film and Adaptive neuron model showed superiority over Burger model in prediction of experimental data. The results are vita in material design, life prediction and usage prescription.